Determination of relationship between dolutegravir and trace amine profile, using advanced liquid chromatography tandem mass spectrometry analysis of various tissues - Henning, Natasha (Stellenbosch : Stellenbosch University, 2023)
Thesis (PhD)--Stellenbosch University, 2023.